Critical Competences for the Management of Post-Operative Course in Patients with Digestive Tract Cancer: The Contribution of MADIT Methodology for a Nine-Month Longitudinal Study - Eleonora Pinto; Alessandro Fabbian; Rita Alfieri; Anna Da Roit; Salvatore Marano; Genny Mattara; Pierluigi Pilati; Carlo Castoro; Marco Cavarzan; Marta Silvia Dalla Riva; Luisa Orrù; Gian Piero Turchi (Behavioral Sciences, 2022)
There is a high postoperative morbidity rate after cancer surgery, that impairs patients’ self-management, job condition and economic strength. This paper describes the results of a peculiar psychological intervention on patients undergoing surgery for esophageal, gastric and colorectal cancer. The intervention aimed to enhance patients’ competences in the management of postoperative daily life. A narrative approach (M.A.D.I.T.—Methodology for the Analysis of Computerised Text Data) was used to create a questionnaire, Health and Employment after Gastro-Intestinal Surgery—Dialogical Questionnaire, HEAGIS-DQ, that assesses four competences. It was administered to 48 participants. Results were used as guidance for specific intervention, structured on patients’ competence profiles. The intervention lasted nine months after surgery and was structured in weekly to monthly therapeutic sessions. Quality of Life questionnaires were administered too. At the end of the intervention, 94% of patients maintained their job and only 10% of patients asked for financial support. The mean self-perception of health-related quality of life was 71.2. The distribution of three of four competences increased after nine months (p < 0.05). Despite economic difficulties due to lasting symptoms after surgery, and to the current pandemic scenario, a structured intervention with patients let them to resume their jobs and continue activities after surgery.